The efficacy of topical aminophylline in local fat reduction: A systematic review - Abdi Dezfouli, Ramin; Hosseinpour, Ali; Qorbani, Mostafa; Daneshzad, Elnaz (Frontiers in Endocrinology, 2023)
Aims: Some studies have reported that the topical forms of aminophylline appear to be relatively effective on local fat burning while having no side effects. This systematic review accumulates all the data on the local fat-burning potency of aminophylline topical formulation. Methods: Documents were retrieved from PubMed, Web of Science, and Scopus databases until Aug 2022. Data were extracted from clinical trials reporting the reduction in thigh or waist circumference as a result of using topical forms containing aminophylline. Screening of included studies was performed independently by two authors, and the quality assessment of included studies was performed based on the Cochrane Collaboration's approach. Results: Of the 802 initial studies, five studies were included in the systematic review. Except for one study, all other studies reported that all participants lost more fat in the treated area than the control groups. The amount of fat reduction differed in studies regarding their different aminophylline concentrations and administration routines. In the case of side effects, except for some studies reporting skin rashes, other studies reported no significant side effects at all. Conclusions: Aminophylline topical formulation offers a safe and effective approach for localized fat reduction.